Використання хмарних технологій для аналізу ефективності омніканальних стратегій - Потапенко, А. О.; Сердюк, Н. М. (ХНУРЕ, 2025)
This work explores the role of cloud computing in analyzing omnichannel marketing strategies. Cloud technologies integrate data, process large datasets, and enable real-time analysis. Platforms like Google BigQuery and AWS Redshift optimize marketing insights. AI and machine learning enhance customer behavior prediction. Key challenges include data securІТy, regulatory compliance, and cost management, addressed through encryption, API integrations, and serverless computing. Cloud analytics improve marketing efficiency and customer experience, wІТh future research focusing on AI-driven personalization and advanced attribution models.
Keywords: хмарна технологія; омніканальна стратегія